TINJAUAN HUKUM EKONOMI SYARIAH TENTANG PENGGUNAAN ROBO ADVISOR DALAM ISLAMIC WEALTH MANAGEMENT (Studi Pustaka Robo Advisor di Indonesia Tahun 2022) - Irawan, Bambang; Maimun, Maimun; Faizal, Liky; Zaki, Muhammad (Fakultas Syariah INSURI Ponorogo, 2023)
Robo advisor is a technology that can assist investors in managing their portfolios. In the context of Islamic finance, transactions and business relationships must ensure compliance with Sharia principles in order to preserve wealth and meet needs. The use of robo advisors in this context has not been extensively researched. This study aims to determine the use of robo advisors in Islamic wealth management. The research method used is literature review with a normative approach and descriptive-analytical analysis. The data used are from literature on the use of robo advisors and Islamic wealth management in Indonesia over the past five years. Based on the workings of robo advisors, various benefits and limitations are found in their use. The conclusion of the analysis of maṣlaḥah (public interest), functionality, and the urgency of using robo advisors shows that their use in Islamic wealth management can be considered permissible as a means for retail investors and beginners to safeguard wealth (ḥifẓ al-mâl) by applying filters for Sharia-compliant investment instruments and adhering to prohibitions on riba (usury), gharar (uncertainty), maysir (gambling), and haram (forbidden). The research recommendation is to conduct further research on the technical aspects and algorithms used by robo advisors in selecting Sharia-compliant investment instruments, and a sound framework of supervision and regulation is needed to ensure the compliance of robo advisors with Sharia principles and the protection of investors' interests.